Calibration of the parameters of the kelvin model generalized in the non-confined static fluency test for asfaltic mixtures by optimization (2018)
Whit this article we show the calibration of parameters of a generalized kelvin model adapted for the simulation of specific data for the unconfined static creep test applied in the viscoelastic characterization of asphalt mixtures. The calibration is performed using the adaptation of an optimization system along with the placement method where the latter serves as the determination of the parameters of the Dirichlet series representative of the generalized kelvin model. The results obtained are very satisfactory and validate the correct formulation and easy implementation of the calibration system in worksheet. © 2006-2018 Asian Research Publishing Network (ARPN).